Investigation on the degradation indicators of short-circuit tests in 1.2 kV SiC MOSFET power modules. (September 2018) - Du, H.; Reigosa, P.D.; Iannuzzo, F.; Ceccarelli, L.
Abstract: This paper provides a comprehensive investigation on both static characteristics and short-circuit performance of 1.2 kV SiC MOSFET power modules with 2nd generation planar technology. The experimental approach is based on the static characteristics measurements and the short-circuit tests with gradual increase of pulse time duration. If any variation of the static characteristics appears, the time duration of next short-circuit tests would keep the same with the last pulse duration (approach 1) or increase continuously (approach 2). The results of the short-circuit waveforms show a gate degradation which is further confirmed with the measurement of the gate leakage current. Additionally, other degradation indicators, including positive shift of threshold voltage, drain leakage current and on-state resistance increase are evidenced and discussed in this paper. These can be used for early prediction of the degradation and failure in the short-circuit conditions. Highlights: The impact of the short-circuit events on the static characteristics of SiC MOSFET power module are analysed. The threshold voltage, on-state resistance, gate and drain leakage current are measured as the degradation indicators. Based on the static characterizations and short-circuit tests with increasing time duration, two approaches are performed. The hypothesis of a conducting path formed through the oxide is confirmed by experimental measurements.